Effect Of Saline Dilution Of Fowl Semen And Artificial Insemenation In Layer Breeder Hens - Kannan, D.; Saravanan, S.; Muralidharan, J.; Ramesh, V.; Kumar, V. Ramesh Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The study was conducted to assess the effect of saline dilution of fowl semen for artificial insemination in egg layer breeder hens under the prevailing environmental conditions. The study was conducted in BV300 layer breeding hens. The dilutions were made with normal saline in the ratio of 1:1 and undiluted semen served as control. Three thousand two hundred and fifty (3250) hens were assigned at random to each group. The dose of insemination was 0.05 ml and the hens were inseminated artificially twice in a week in the afternoon between 1430 h and 1730 h. It was found that the hens in saline dilution group produced significantly (P < 0.05) less infertile eggs than the hens in undiluted semen group. Besides, diluted semen inseminated group had numerically lesser early embryonic mortality per cent, dead in shell per cent, lesser live in shell per cent, lesser chicks culling per cent and increased hatchability and saleable female chicks. The present study provided evidence that hens inseminated with 1:1 semen dilution produced more fertile eggs compared to those hens inseminated with undiluted semen. Additionally, insemination with saline diluted semen group had reduced the cost by 0.47 per female chick.
Keywords: Layer parents; Semen dilution; Fertility; Economics